In-Water Cleaning and Capture to Remove Ship Biofouling: An Initial Evaluation of Efficacy and Environmental Safety - Tamburri, Mario N.; Davidson, Ian C.; First, Matthew R.; Scianni, Christopher; Newcomer, Katherine; Inglis, Graeme J.; Georgiades, Eugene T.; Barnes, Janet M.; Ruiz, Gregory M. (Frontiers in Marine Science, 2020)
Biofouling is a long-standing challenge for ships because it can interfere with operations and increases vessel drag, fuel consumption and exhaust emissions. More recently, ship biofouling has also been recognized as a leading vector for global transfers and introductions of marine non-indigenous species. Ship in-water cleaning and capture (IWCC) systems, to remove and collect macrofouling organisms and associated antifouling coating compounds, are now becoming available as a possible solution to both problems. However, independent and rigorous evaluations of IWCC efficacy and environmental safety are needed to facilitate technology maturation, support vessel operator biofouling management decisions, aid IWCC approvals and permitting, and future biosecurity regulations. We developed a formal protocol for evaluating an IWCC system, on two ships with varying biofouling levels and under different environmental conditions, to quantify biofouling removal and capture efficacy as well as impacts on water quality. The IWCC system reduced hull biofouling by 82 - 94%. Concentrations of dissolved and particulate Cu and Zn in effluent from the IWCC onshore processing varied by orders of magnitude between trials, in one case greatly exceeding water quality standards. Our results demonstrate that rigorous, quantitative assessments of IWCC system performance are possible, even under challenging conditions. This initial evaluation also identifies the major factors that impact performance of in-water cleaning, and key needs for future research, to consider in advancing standardized testing and independent evaluations needed for all in-water cleaning systems.